Pengaruh Efektivitas Pemanfaatan E-Learning Madrasah Dan Minat Belajar Terhadap Prestasi Belajar Ekonomi Siswa Madrasah Aliyah Negeri Jakarta Timur - Adela Adela; Ari Saptono; Aditya Pratama (Jurnal Ilmiah Wahana Pendidikan, 2022)
Research with this approach aims to describe the direct and indirect effects of Madrasah E-Learning Utilization Effectiveness on Learning Interest and Economic Learning Achievement, as well as Learning Interest as a variable between the Effectiveness of Madrasah E-Learning Utilization and Economic Learning Achievement. The population in this study was the students of Madrasah Aliyah Negeri in East Jakarta with the affordable population being students of MAN 9 Jakarta and MAN 18 Jakarta with a total of 180 students being the sample. The data was obtained using a questionnaire of 36 statements using a Likert scale with 5 alternative answers, which were distributed through a google form, as well as data on the ratio of the value of students' economics subjects. Then the learning data used path analysis with the help of IBM SPSS Version 25 software. The results showed that: (1) There was a direct influence on the effectiveness of Madrasah E-Learning Utilization on Economics Learning Achievement, (2) There was a direct influence of Interest on Economics Learning Achievement, (3) There is a direct influence on the effectiveness of Madrasah E-Learning Utilization on Learning Interests, and (4) There is an indirect effect on the effectiveness of Madrasah E-Learning Utilization on Economic Learning Achievement through Learning Interests